ErbSiHM 0.1 - Henriette Houben; Ralf Maiterth (Arbeitskreis Quantitative Steuerlehre (arqus), 2010)
This contribution describes ErbSiHM 0.1 which is an inheritance tax simulation model. ErbSiHM 0.1 comprises of a microsimulation model based on the data of the German Inheritance Tax Statistics 2002 and a group simulation model employing the data of the SOEP. The microsimulation model of ErbSiHM 0.1 allows for detailed analyses of revenue and distributional effects of the German inheritance tax or inheritance tax reform proposals. In addition the impact of the inheritance tax on the tax burden of particular groups of taxpayers can be detected. As the German Inheritance Tax Statistics do not include data of transfers of low-value estates a supplementary group model based on the data of the SOEP has been designed. This SOEP-based supplementary model is in particular useful to estimate revenue effects of tax reforms.
Keywords: 330; Erbschaftsteuer; Mikrosimulation; Steueraufkommen; Steuerinzidenz; Deutschland